2010
DOI: 10.1002/bjs.7137
|View full text |Cite
|
Sign up to set email alerts
|

Randomized clinical trial of mesh versus sutured wound closure after open abdominal aortic aneurysm surgery

Abstract: Mesh placement significantly reduced the rate of postoperative incisional hernia after open AAA repair without increasing the rate of complications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
68
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 155 publications
(71 citation statements)
references
References 18 publications
3
68
0
Order By: Relevance
“…Two studies reported data on operation time [35,36]; however, as the study by Bevis et al [35] did not report standard deviations, these results could not be pooled. Bevis et al [35] reported no statistically significant difference in median duration of operation (min) between the PMA group and the PS group (150 min, range 90-225 vs. 140 min, range 90-300; p = 0.59).…”
Section: Resultsmentioning
confidence: 39%
See 4 more Smart Citations
“…Two studies reported data on operation time [35,36]; however, as the study by Bevis et al [35] did not report standard deviations, these results could not be pooled. Bevis et al [35] reported no statistically significant difference in median duration of operation (min) between the PMA group and the PS group (150 min, range 90-225 vs. 140 min, range 90-300; p = 0.59).…”
Section: Resultsmentioning
confidence: 39%
“…The study by Bevis et al [35] was the only study that performed a power analysis prior to the start of trial. Unfortunately, they were not able to reach the number of patients calculated, and thus the study remained underpowered.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations